PERANCANGAN SISTEM INFORMASI BIMBINGAN KONSELING BERBASIS WEB MENGGUAKAN PHP DAN MYSQL DI SMK ITIKURIH HIBARNA - Nina Amalia; Ela Wangi (INFOKOM (Informatika & Komputer), 2018)
Currently counceling guidance in SMK Itikurih Hibarna still using manually system. Therefore, neccessary counceling guidance information system design with more intregated database in order to development of students can evaluate optimally and effective reportings The research method is using observation method and literature study, while the design method using orientation object oriented method with modelling UML (Unified Modelling Language) and implementation with programming language PHP and Mysql database along with application development method using waterfall. Suggestion given as follows : 1.Implement a web-based information system to make easier and faster in counceling data processing , 2. With web-based information system counceling guidance, the development of students can access everywhere and everytime 3.Develop a system to be better and optimal.